Collective judging in comparative perspective : counting votes and weighing opinions / edited by Birke Häcker, Wolfgang Ernst. - Häcker, Birke, 1977-; Ernst, Wolfgang, 1956- (Intersentia studies on courts and judges, 2020)
This book provides insight into modern collective judicial decision-making. Courts all over the world sit in panels of several judges, yet the processes by which these judges produce the courts' decisions differ markedly. Judges from some of the world's most notable judicial bodies, in both the civilian and the common law tradition and from supra-/international courts, share their experiences and reflect on the challenges to which their collective endeavour gives rise. They address matters such as the question of panel constitution, the operation of rapporteur systems, pre- and post-hearing conferences, the hearing procedure itself, the nature of the interaction between the judicial panel and parties' advocates, the extent to which a unitary judgment of the court or at least a single majority judgment is required or deemed desirable, and how it is ultimately arrived at through different voting mechanisms. The judicial views are supplemented by a number of academic commentaries. Collective Judging in Comparative Perspective serves as an inspiration for future court design. Sir Jack Beatson (formerly Court of Appeal of England and Wales) Thomas von Danwitz (Court of Justice of the European Union) Matthew Dyson (University of Oxford) Harry T Edwards (United States Court of Appeals for the DC Circuit) Wolfgang Ernst (University of Oxford) Kevin Garnett QC (formerly Boards of Appeal of the European Patent Office) Msgr Markus Graulich (Pontifical Council for Legislative Text) Beate Gsell (Ludwig-Maximilians-Universität Munich) Birke Häcker (University of Oxford) Dominique Hascher (Cour de cassation) Sir Launcelot Henderson (Court of Appeal of England and Wales) Rchard Hyland (Rutgers Law School) Susan Kiefel AC (High Court of Australia) Georg Kodek (Austrian Supreme Court) James Lee (King's College London) Sir Keith Lindblom (Court of Appeal of England and Wales) Gertrude Lübbe-Wolff (formerly German Federal Constitutional Court) Theodor Meron (International Residual Mechanism for Criminal Tribunals) Angelika Nussberger (formerly European Court of Human Rights) Akira Ojima (Chief Judicial Research Official, Supreme Court of Japan) Naoki Onishi (Otsu District Court, Japan) Christos Ravanides (Office of Legal Affairs, United Nations) Lord Reed of Allermuir (Supreme Court of the United Kingdom) Thomas Rüfner (University of Trier) Johanna Schmidt-Räntsch (German Federal Court of Justice) Thomas Stadelmann (Swiss Supreme Court) Wolfgang Ernst is Regius Professor of Civil Law, University of Oxford, and Fellow of All Souls College.Birke Häcker is the Professor of Comparative Law, University of Oxford, and Fellow of Brasenose College.